Catalytic and Spectroscopic Properties of the Halotolerant Soluble Methane Monooxygenase Reductase from Methylomonas methanica MC09. (13th January 2022) - Lettau, Elisabeth; Zill, Domenic; Späth, Marta; Lorent, Christian; Singh, Praveen K.; Lauterbach, Lars
Abstract: The soluble methane monooxygenase receives electrons from NADH via its reductase MmoC for oxidation of methane, which is itself an attractive C1 building block for a future bioeconomy. Herein, we present biochemical and spectroscopic insights into the reductase from the marine methanotroph Methylomonas methanica MC09. The presence of a flavin adenine dinucleotide (FAD) and [2Fe2S] cluster as its prosthetic group were revealed by reconstitution experiments, iron determination and electron paramagnetic resonance spectroscopy. As a true halotolerant enzyme, MmoC still showed 50 % of its specific activity at 2 M NaCl. We show that MmoC produces only trace amounts of superoxide, but mainly hydrogen peroxide during uncoupled turnover reactions. The characterization of a highly active reductase is an important step for future biotechnological applications of a halotolerant sMMO. Abstract : The reductase module of the soluble methane monooxygenase from Methylomonas methanica MC09 is catalytically active for NADH oxidation even at high salt concentrations. Spectroscopic analyses revealed one FeS cluster and FAD. During uncoupled turnover reactions, moderate levels of hydrogen peroxide were released. The characterization of this reductase is an important step for future biotechnological applications of a halotolerant sMMO.